RP-HPLC Method Development and Validation for the Determination and Stability Indicative Studies of Montelukast in Bulk and its Pharmaceutical Formulations - A. Patnaik; S. S. Panda; S. Sahoo; V. J. Patro (E-Journal of Chemistry)
A simple, precise, accurate, economical and reproducible HPLC method for estimation of montelukast in tablet dosage form has been developed. Quantitative HPLC was performed with Shimadzu LC2010c HT with Winchrom Software with UV-Visible detector (SPD-IOA), PUMP (LC-IOAT) and (LC-IOATvp). Phenomenex C8, 5 μm, 25 cm × 4.6 mm i.d. column was used in the study. The mobile phase of ACN: Acetate buffer= 6.5:3.5 of pH 3 were used in this study. The conditions optimized were: flow rate (1 mL/minute), wavelength (222 nm) and run time was 20 min. Retention time was found to be 3.08 min. The linearity was found to be in the concentration range of 10-100 μg/mL. The developed method was evaluated in the assay of commercially available tablet moni containing 10 mg of montelukast. The amount of drug in tablet was found to be 10.34 mg/tab for the brand. Results of analysis were validated statistically and by recovery studies. The recovery studies 99.67% was indicative of the accuracy of proposed method. The precision was calculated as repeatability, inter and intraday variation (%RSD) for the drug. By using the method, stability of the drug has been studied.